A system based on the NICTs for aid blind and people with vision impaired in their hiking route for unknown locations (Research, Society and Development, 2017)
The aim of the work is to analyze a mobility system for visually impaired people on their route to the place where they want to go.. It was checked what is in the state of art in the mobility and accessibility area for visually impaired. It was made the study of the behavior of the visually impaired and interviews with them were made in order to know what they think about the use of the new technologies of information and communication, helping us in the development of this system. In order to reach our general goal it was made a study of the mobile computing technologies, like voice recognition, GPS (Global Positioning System), the Android and Arduino platform. We used software engineering for the analysis, design and implementation of the system. Finally tests were done to validate the functionality and reliability of the system. When an object was approached to the infrared sensor, there was a beep warning of such proximity, and the maximum identification distance was approximately 0.8m. With this maximum distance of identification, the visually impaired person has enough time to deviate from the obstacle ahead. It can be concluded, then, that the identification of obstacles meets what was proposed.